(3SQGL Gdedhcs - (3CHh HcQ Hf GdhdjO GdagQj GdWQWhTjs ((3GHh GdaVd eMeO Hf YHO GdcQje GdSGYGJi GdegfOS s)
(3ChdgG (B:s
(3jHOC HGdHGH GdChd ai ehGYX Gdedhc s
(3BNQgG (B:s
(3jfJgi HGdHGH GdQGHY hGdSJhf hjTJed Ydi Mce efKhQ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B984s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs